Role of Antioxidants in Alleviating Bisphenol A Toxicity - Shehreen Amjad; Md Saidur Rahman; Myung-Geol Pang (Biomolecules, 2020)
Bisphenol A (BPA) is an oestrogenic endocrine disruptor widely used in the production of certain plastics, e.g., polycarbonate, hard and clear plastics, and epoxy resins that act as protective coating for food and beverage cans. Human exposure to this chemical is thought to be ubiquitous. BPA alters endocrine function, thereby causing many diseases in human and animals. In the last few decades, studies exploring the mechanism of BPA activity revealed a direct link between BPA-induced oxidative stress and disease pathogenesis. Antioxidants, reducing agents that prevent cellular oxidation reactions, can protect BPA toxicity. Although the important role of antioxidants in minimizing BPA stress has been demonstrated in many studies, a clear consensus on the associated mechanisms is needed, as well as the directives on their efficacy and safety. Herein, considering the distinct biochemical properties of BPA and antioxidants, we provide a framework for understanding how antioxidants alleviate BPA-associated stress. We summarize the current knowledge on the biological function of enzymatic and non-enzymatic antioxidants, and discuss their practical potential as BPA-detoxifying agents.